Comparative transcriptomic analysis of primary endometrial cancer and bone metastatic cancer: metastasis-associated genes and abnormal cell cycle regulation - Qinmin Wu; Feng Li; Yunlong Zhang; Siying Li; Chuan Xiang (Discover Oncology)
Abstract Endometrial cancer (EC) is the most common tumor of the female reproductive system. Its incidence is rising worldwide. Bone metastasis (BMs) in EC is rarely reported, and is seen in only 0.8% of patients. Once bone metastasis develops, it often indicates a poor prognosis. Current research on the bone metastasis of primary tumors suggests that tumor cells primarily colonize bones through hematogenous metastasis and are stimulated to grow by the bone microenvironment. However, the biological mechanism of bone metastasis in EC remains unclear. In this study, we aim to determine the changes in gene expression profiles in EC bone metastasis and explore the transcriptomic differences between metastatic and primary lesions. We collected one primary EC case and two bone metastasis tumors for transcriptomic analysis. The analysis revealed that numerous genes are involved in regulating the cell cycle and proliferation. Analysis of differentially expressed genes (DEGs) revealed that these genes are involved in the regulation of post-translational modification, protein turnover, and signal transduction mechanisms. E2F1, MCM2, RFC2, and ICAM1 are involved in the metastasis and progression of EC with bone metastasis (ECBM). The Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis indicates significant changes in the Hippo signaling pathway, which regulates cell proliferation, and in the cell adhesion signaling pathway. Numerous transcription factors, including SOX2, NUSAP1, and ACTA1, which promote tumor development, are involved in regulating the expression of cell cycle control genes. Survival curve analysis of high-expression cell cycle genes, including P27, P19, and CDK1, in ECBM showed that elevated levels of these genes are associated with poorer patient survival. Our research identified genes and key signaling pathways associated with bone metastasis. These findings provide a theoretical basis for the treatment of bone metastasis in EC.